From land to sea: a new high-resolution bathymetry and topography of the Campi Flegrei area, Southern Italy - Roberto Gianardi; Marina Bisson; Luca Cocchi; Roberto Isaia; Salvatore Passaro; Vincenzo Sepe; Claudia Spinetti (Journal of Maps)
Campi Flegrei is an active volcanic area located in the Campanian region (southern Italy). It is characterized by a caldera structure including a subaerial portion densely populated and a submarine area represented by the Gulf of Pozzuoli. Altimetry data acquired by Airborne Laser Scanning and seafloor depth data coming from several bathymetry surveys were used to show a Digital Elevation Model with a spatial resolution of 1 m for the topography of Campi Flegrei. This model, for the first time, reconstructs a topographic continuum from land to seafloor for a total extent of 138.32 km2. Thanks to the high spatial resolution, the model allowed to map and measure seafloor features such as landslides and terraces as well as Roman-epoch artefacts. Our results provide accurate reference topography for a more complete mapping and modelling of natural hazards that affect, directly or indirectly, the entire area of the Campi Flegrei caldera.